TINJAUAN HUKUM PENOLAKAN PENGENAAN BEA MASUK ANTI DUMPING TERHADAP PRODUK BAJA LAPIS ALUMINIUM SENG OLEH KEMENTERIAN PERDAGANGAN: Legal Review of Rejection of The Impostion of ANTI-DUMPING Import Duty on Alumunium Zinc Coated Steel Products - Muhammad Firmandhana Jati Kusuma; Rosdiana Saleh (Reformasi Hukum Trisakti, 2024)
Dumping is harmful to local industries as significant price differences make consumers prefer dumped products with similar or better quality over local or non-dumping imported products, crippling domestic competitors. To address this, anti-dumping duties are applied to protect domestic industries. However, anti-dumping duties are often rejected based on national interests, which should ideally protect local industries. Problem formulation in this research is this study examines whether the rejection of anti-dumping duties on aluminum and zinc-coated steel is justified and its legal consequences. This normative research uses secondary data, descriptive analysis, and deductive reasoning. Research results and discussion and conclusions shows that the rejection basis is incorrect as it fails to consider the negative impact on domestic industries. The decline in market share and sales during the investigation period indicates that imports from China and Vietnam have financially harmed local industries. As a consequence, Indonesia risks facing trade sanctions such as increased export tariffs, which could negatively impact domestic production and productivity, ultimately weakening its economic competitiveness. Thus, protecting national interests should not overlook the damage experienced by local industries.